Chromosomal Spreading of Microsatellites and (TTAGGG)(n) Sequences in the Characidium zebra and C. gomesi Genomes (Characiformes: Crenuchidae) - Pucci, Marcela B. (2016)
Sex chromosome evolution involves the accumulation of repeat sequences such as multigenic families, noncoding repetitive DNA (satellite, nninisatellite, and microsatellite), and mobile elements such as transposons and retrotransposons. Most species of Characidium exhibit heteromorphic ZZ/ZW sex chromosomes; the W is characterized by an intense accumulation of repetitive DNA including dispersed satellite DNA sequences and transposable elements. The aim of this study was to analyze the distribution pattern of 18 different tandem repeats, including (GATA)(n) and (TTAGGG)(n), in the genonnes of C. zebra and C. gomesi, especially in the C. gomesi W chromosome. In the C. gomesi W chromosome, weak signals were seen for (CAA)(10), (CAC)(10) (CAT)(10), (CGG)(10), (GAC)(10), and (CA)(15) probes, (GA)(15) and (TA)(15) hybridized to the autosomes but not to the W chromosome. The (GATA), probe hybridized to the short arms of the W chromosome as well as the (CG)(15) probe, The (GATA)(n) repeat is known to be a protein-binding motif. GATA-binding proteins are necessary for the decondensation of heterochromatic regions that hold coding genes, especially in some heteromorphic sex chromosomes that may keep genes related to oocyte development. The (TAA)(10) repeat is accumulated in the entire W chromosome, and this nnicrosatellite accumulation is probably involved in the sex chronnosonnedifferentiation process and crossover suppression in C. gomesi. These additional data on the W chromosome DNA composition help to explain the evolution of sex chromosomes in Characidium. (C) 2016 S. Karger AG, Basel